2011
DOI: 10.11646/zootaxa.3092.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Advertisement and release calls in Neotropical toads of the Rhinella granulosa group and evidence of natural hybridization between R. bergi and R. major (Anura: Bufonidae)

Abstract: The Rhinella granulosa group currently includes 12 species distributed eastern to the Andes, from Panama to central Argentina. We studied bioacoustic features of the advertisement calls in seven of these species: Rhinella azarai, R. bergi, R. centralis, R. dorbignyi, R. fernandezae, R. major, and R. merianae. In addition, we analyzed the release calls of R. azarai, R. bergi, R. dorbignyi, and R. fernandezae. The advertisement calls consisted of long trills, composed by notes with a variable pulse number (2–8) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 0 publications
1
23
1
1
Order By: Relevance
“…Heyer et al (1996), for example, while revising the taxonomic status of the Leptodactylus mystaceus species complex recognized a new sibling species differentiated by the advertisement call. Guerra et al (2011) analysed the advertisement calls of the Rhinella granulosa species group and corroborated a recent morphology-based taxonomy (Narvaes and Rodrigues, 2009). Several other similar examples abound in the literature (Pombal-Jr. and Haddad, 1999;Abrunhosa et al, 2005;Canedo and Pombal-Jr., 2007;Glaw et al, 2010).…”
Section: Introductionsupporting
confidence: 59%
“…Heyer et al (1996), for example, while revising the taxonomic status of the Leptodactylus mystaceus species complex recognized a new sibling species differentiated by the advertisement call. Guerra et al (2011) analysed the advertisement calls of the Rhinella granulosa species group and corroborated a recent morphology-based taxonomy (Narvaes and Rodrigues, 2009). Several other similar examples abound in the literature (Pombal-Jr. and Haddad, 1999;Abrunhosa et al, 2005;Canedo and Pombal-Jr., 2007;Glaw et al, 2010).…”
Section: Introductionsupporting
confidence: 59%
“…Guerra et al. () reported the occurrence of hybrids between both species calling actively in breeding sites, and some other adult specimens with intermediate morphological traits between these species were observed in collection material (M.O.P. and D.B., pers.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest a wide introgression of nuclear genes between Rhinella bergi and R. major throughout extensive geographical areas, which is supported by the large number of polymorphisms in the nuclear sequences of both species (Appendices S9.1-S9.6) from different (and sympatric) localities. Guerra et al (2011) reported the occurrence of hybrids between both species calling actively in breeding sites, and some other adult specimens with intermediate morphological traits between these species were observed in collection material (M.O.P. and D.B., pers.…”
Section: Nuclear-mitochondrial Discordancementioning
confidence: 99%
See 2 more Smart Citations